Qualitative Evidence in Trauma Research: The Case of the Journal of Traumatic Stress - Keats, Patrice A.; Keats-Osborn, William R. (Canadian Journal of Counselling and Psychotherapy, 2013)
The debate over the relative merits of qualitative and quantitative methods is particularly salient in the helping professions, where day-to-day clinical practice is potentially informed by research. Despite the growth in the use of qualitative methods and increasing recognition of their usefulness and relevance, particularly since the development of standards for evaluating their quality, the ratio of qualitative to quantitative articles published in journals within the helping professions tends to be small. In the context of previous studies that have shown that editorial interest in qualitative research considerably outweighs qualitative submissions and publications, we examine articles in the Journal of Traumatic Stress (JTS) to determine whether this pattern extends to the field of traumatic stress studies. Findings indicate that despite consistent interest in multidisciplinary approaches—including qualitative designs—expressed by the journal’s editors, the publication of qualitative articles in the JTS has declined since 1988. Potential explanations and effects of this discrepancy are offered.